2019
DOI: 10.1111/1365-2745.13137
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying niche availability, niche overlap and competition for recruitment sites in plant populations without explicit knowledge of niche axes

Abstract: Niche availability, niche overlap and competitive ability are key determinants of the distribution and abundance of species. However, quantifying each of these components is difficult because it is not always possible to identify or measure relevant environmental gradients (niche axes) along which species might partition or compete for niche space. We describe a method that uses seed addition experiments to quantify the number of ‘safe‐sites’ (microsites suitable for a species to recruit from seed) at a locati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 50 publications
(79 reference statements)
0
26
0
Order By: Relevance
“…The colour spectrum follows the distribution range maps (Figure 1) et Brown, 1984;Kambach et al, 2019;Sheth et al, 2020;Slatyer et al, 2013), we found no significant relationship between range size and the biotic and climatic niche breadth estimates for the species in the globally important tree genus Fagus. or biotic interactions with other species, the regional availability of suitable niche space or differences in landscape heterogeneity, evolutionary processes or historical events, as well as human impacts (Boulangeat et al, 2012;Lambdon, 2008;Sillero, 2011;Slayter et al, 2013;Wandrag et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The colour spectrum follows the distribution range maps (Figure 1) et Brown, 1984;Kambach et al, 2019;Sheth et al, 2020;Slatyer et al, 2013), we found no significant relationship between range size and the biotic and climatic niche breadth estimates for the species in the globally important tree genus Fagus. or biotic interactions with other species, the regional availability of suitable niche space or differences in landscape heterogeneity, evolutionary processes or historical events, as well as human impacts (Boulangeat et al, 2012;Lambdon, 2008;Sillero, 2011;Slayter et al, 2013;Wandrag et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…; Wandrag et al . in press). Because a set mass (rather than number) of seeds was added to seeded subplots, the seed mass‐number trade‐off remained intact in our experiment, such that light‐seeded invaders would have had more seeds than heavier seeded species, and thus more opportunities to recruit (Duncan et al .…”
Section: Discussionmentioning
confidence: 99%
“…; Wandrag et al . in press). The relative advantage of lighter, more numerous seeds was apparent for occupancy (where hierarchical distance was significant), but not abundance, the latter of which was mostly strongly related to seed mass CWM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We conducted a seed removal experiment in Austral summer 2018 in grassland on the University of Canberra campus, ACT. We selected three native ( Bothriochloa macra , Chloris truncata , Rytidosperma caespitosum ) and three exotic ( Dactylis glomerata , Eragrostis curvula , Phalaris aquatica ) grass species that co‐occur locally (Wandrag et al ., 2019). Seeds of the three native species have conspicuous awns (Fig.…”
Section: Methodsmentioning
confidence: 99%